Exploratory Medico-Legal Assessment of Health Trajectories in a Cohort of Italian Inmates: A Retrospective Study - Massimiliano Esposito; Federica Ministeri; Mario Giuseppe Chisari; Lucio Di Mauro; Serena Matera; Valentina Schilirò; Ermanno Vitale; Francesco Sessa; Giuseppe Ragazzi; Carmelo Ferrara; Cristoforo Pomara (Forensic Sciences, 2026)
Background: Health assessment in custodial settings represents a core medico-legal function, particularly when clinical changes may influence detention compatibility and judicial decisions. Objective documentation of disease progression during incarceration is essential to ensure respect for the principle of healthcare equivalence and the protection of fundamental rights. Methods: A retrospective descriptive medico-legal analysis was conducted on 37 male inmates referred for forensic evaluation. Standardized assessments included anamnesis, physical and psychiatric examination, evaluation of medical records, and comparative evaluation of pre-detention and detention-period health status. Results: Pre-existing conditions accounted for 73% of pathologies, while 27% developed during imprisonment. Clinical deterioration occurred in 35.1% of inmates (13 cases). Psychiatric disorders were frequent (27%, 10 inmates), predominantly depressive. Conclusions: The findings indicate that imprisonment may constitute a setting that contributes to the progression of medical and psychiatric conditions, highlighting structural and organizational challenges within penitentiary healthcare. Strengthening standardized medico-legal assessment protocols, improving multidisciplinary collaboration, and ensuring continuity of care between prison and community health services are crucial steps toward protecting inmates’ health. This study provides an exploratory assessment of health conditions in a cohort of inmates within the Italian correctional system, emphasizing the central role of healthcare in custodial settings. Since many Italian correctional facilities are equipped with well-developed healthcare services and appropriate diagnostic and therapeutic resources, numerous acute and chronic medical conditions can be effectively managed within the prison setting, ensuring continuity of care while limiting the need for transfer to external healthcare facilities.